Determination of Nursing Students’ Pelvic Floor Health Knowledge Levels - Mamuk, Rojjin; Miral, Mukaddes; Dişsiz, Melike; Bal, Meltem Demirgöz (My University, 2022)
Objective: This study aimed to investigate the pelvic floor health (PFH) knowledge levels of third and fourth grade nursing students. Methods: This descriptive and cross-sectional study was conducted with a sample of 167 students who were enrolled in the third and fourth classes year of the Nursing Department of two foundation universities and met the research criteria. The inclusion criteria were being enrolled in the third and fourth classes year of the Nursing Department, to have taken the course of Obstetrics and Gynecology Nursing and agreeing to participate in the study. Data were collected face to face interview through the “Personal Information Form” and the “Pelvic Floor Health Knowledge Quiz (PFHKQ)”. Statistical analyzes were obtained by using number, percentage, mean, students’ t-test and one-way analysis of variance in SPSS package program. Results: 50.3% of the students stated that they had moderate knowledge of PFH, 19.2% applied pelvic floor exercises (PFE), 18% informed patients and healthy individuals about PFH, and 21% took part in the care processes of patients with pelvic floor dysfunction. The total mean score obtained from the PFHKQ was found 16,29±7,00. In addition, the mean of the Function/ Dysfunction sub-dimension of the scale was 4.40±1.98, in the Risk/Etiology sub-dimension 6.83±3.42, and 5.04±2.36 in the Diagnosis/Treatment sub-dimension. Conclusion: In this study, the knowledge of nursing students about PFH is a moderate level. The rates of applying PFE and informing the individuals about PFH are low.
Keywords: Sağlık Bilimleri ve Hizmetleri; Hemşirelik